Eksperimen Material Pada Masker NonMedis dengan Memperhatikan Faktor Komunikasi Nonverbal dan Estetika - Pingki Indrianti; Oki Kurniawan (JURNAL RUPA, 2021)
Since the COVID-19 pandemic, the Indonesian government has implemented the 5M health protocol (washing hands, maintaining distance, wearing masks, avoiding crowds, maintaining body immunity). Along with the appeal for the use of masks for the general public, non-medical covers made of cloth (cloth masks) with various and unique designs have emerged, specifically to support a lifestyle. From the results of observations through several sources, there is another need for cloth masks, namely for nonverbal communication on facial expressions (facial kinesics). When using a mask, facial expressions are often invisible, especially in mouth movements (lips). This nonverbal communication will undoubtedly be needed for both the deaf and speech-impaired people and society in general. This study aims to determine the characteristics of non-medical cloth mask materials that can support the convenience of facial kinesic non-verbal communication. The material is also considered in terms of visual aesthetics so that the mask can still keep the appearance of everyday attire. This study uses a qualitative approach with experimental methods on several non-medical masks with various material variations. The results showed that masks with a combination of transparent materials such as synthetic organza dove fabric (polyamide) and PVC plastic were sufficient to help nonverbal communication on facial expressions while still having droplet and aerosol protection. This research needs to be improved by utilizing filtration technology to make the mask more comfortable.